Imaging of crystalline and amorphous surface regions using time-of-flight secondary-ion mass spectrometry (ToF-SIMS): application to pharmaceutical materials - Iuras, Andrea; Scurr, David J.; Boissier, Catherine; Nicholas, Mark L.; Roberts, Clive J.; Alexander, Morgan R. (American Chemical Society, 2016)
The structure of a material, in particular the extremes of crystalline and amorphous forms, significantly impacts material performance in numerous sectors such as semiconductors, energy storage, and pharmaceutical products, which are investigated in this paper. To characterize the spatial distribution for crystalline−amorphous forms at the uppermost molecular surface layer, we performed time-of-flight secondary-ion mass spectroscopy (ToF-SIMS) measurements for quench-cooled amorphous and recrystallized samples of the drugs indomethacin, felodipine, and acetaminophen. Polarized light microscopy was used to localize crystallinity induced in the samples under controlled conditions. Principal component analysis was used to identify the subtle changes in the ToF-SIMS spectra indicative of the amorphous and crystalline forms for each drug. The indicators of amorphous and crystalline surfaces were common in type across the three drugs, and could be explained in general terms of crystal packing and intermolecular bonding, leading to intramolecular chain scission in the formation of secondary ions. Less intramolecular scission occurred in the amorphous form, resulting in a greater intensity of molecular and dimer secondary ions. To test the generality of amorphous−crystalline differentiation using ToF-SIMS, a different recrystallization method was investigated where acetaminophen single crystals were recrystallized from supersaturated solutions. The findings indicated that the ability to assign the crystalline/amorphous state of the sample using ToF-SIMS was insensitive to the recrystallization method. This demonstrates ToF-SIMS capabilities of detecting and mapping ordered crystalline and disordered amorphous molecular materials forms at micron spatial resolution in the uppermost surface of a material.